A Review: Application of AIOT in Smart Cities in Industry 4.0 and Society 5.0 - Saluky; Yoni Marine (Etunas, 2023)
This review paper explores the application of Artificial Intelligence of Things (AIOT) in smart cities under the contexts of Industry 4.0 and Society 5.0. The main objective of the paper is to analyze and evaluate the latest developments and implementations of AIOT in smart cities, and to provide insights on the potential benefits, challenges, and future research directions. The study uses a systematic literature review approach and synthesizes relevant literature from various sources. The results indicate that AIOT has immense potential to revolutionize the way smart cities operate by enhancing the efficiency, sustainability, and livability of urban spaces. However, the adoption of AIOT also poses several challenges such as security, privacy, and ethical concerns. The paper concludes that a more collaborative and interdisciplinary approach is needed to fully realize the potential of AIOT in smart cities and address the challenges that come with it. The findings of this review provide useful insights for policymakers, practitioners, and researchers interested in the development and implementation of AIOT in smart cities.